Ebola-Related Health Information Wanted and Obtained by Nurses and Public Health Department Employees: Effects of Formal and Informal Communication Channels. (30th June 2020) - Xie, Bo; Zhou, Le (Betty); Yoder, Linda H.; Johnson, Karen E.; Garcia, Alexandra; Kim, Miyong
ABSTRACT: Objectives: The aim of this study was to (1) understand types and amounts of Ebola-related information that health organization employees wanted and obtained through formal, informal, internal, and external organizational communication channels; (2) determine potential discrepancies between information wanted and obtained; and (3) investigate how organizational structure might affect information wanted and obtained through these communication channels. Methods: Primary data were collected from 526 health workers in 9 hospitals and 13 public health departments in Texas from June to November 2015. Survey data were collected for 7 types of Ebola-related information health organization employees wanted and obtained through various types of organizational communication channels. Descriptive statistical analyses, mixed design analysis of variance, regression analyses, and multilevel analyses were used to analyze the data. Results: Hospital employees (mostly nurses in our sample) received more self-care information than they wanted from every communication channel. However, they received less about all other types of information than they wanted from every communication channel separately and combined. Public health department employees wanted more information than they received from every communication channel separately and combined for all 7 types of information. Conclusions: Discrepancies existed between the types of Ebola-related information wanted and obtained by employees of hospitals and public health departments.